(untitled) (REMUNOM, 2026)
Impetigo is a superficial bacterial skin infection caused by Gram-positive bacteria, commonly affecting children aged 2 to 5 years, although it can occur at any age. Clinically, impetigo is divided into two forms: bullous and non-bullous. Bullous impetigo is characterized by the formation of large, fragile blisters (bullae). Non-bullous impetigo presents with vesicles and pustules that rupture, leading to the formation of honey-colored crusts. The described clinical case involves a 12-year-old patient with a history of psoriasis and atopic dermatitis, who presented with scaly and painful vesicular lesions on the lip and perioral area, without an apparent precipitating factor, and associated with systemic symptoms. Due to the persistence of symptoms and following the patient’s multidisciplinary assessment, a bacterial infection was suspected, the condition was diagnosed as non-bullous impetigo. Treatment was initiated with antibiotics, photodynamic therapy, and hygiene measures, resulting in significant improvement and hospital discharge after five days. Thus, it is noted that the patient exhibited a typical presentation of non-bullous impetigo, with the presence of vesicles and pustules that, upon rupture, resulted in the characteristic "honey-colored crusts" of impetigo. However, the case presents some divergences from the literature, notably the severity due to the presence of painful and systemic symptoms, and the patient’s age group, which is older than the most commonly affected demographic. The case highlights the importance of differential diagnosis between impetigo and other skin infections, as well as appropriate therapeutic management to avoid complications and promote complete recovery.